VISUAL COMMUNICATION IN FOOD MARKETING: EXPLORING THE ROLE OF AI-POWERED VISUAL ANALYTICS IN UNDERSTANDING CONSUMER BEHAVIOR (International Journal of Food and Nutritional Sciences, 2022)
Visual communication is crucial in food marketing, significantly influencing consumer behavior and decision-making. With digital media's advent, marketers increasingly rely on visually engaging content to attract and retain customers. This study explores the role of AI-powered visual analytics in understanding consumer behavior within the food marketing domain. This study uses AI technologies such as image recognition, sentiment analysis, and machine learning to investigate how visual content affects consumer engagement, preferences, and perceptions. The research employs a mixed-methods approach, integrating quantitative analysis of consumer engagement metrics with qualitative insights from marketing professionals. Data is collected from various digital platforms, including social media and e-commerce websites, to identify trends and patterns in consumer behavior. The findings highlight the potential of AI-powered visual analytics to enhance the effectiveness of visual communication strategies in food marketing, offering valuable insights for marketers looking to optimize their approaches in the digital age. This study also discusses the implications of AI integration in marketing, its ethical considerations, and the limitations of current methodologies.